PENGARUH KOMPETENSI PEDAGOGIK DAN KOMPETENSI KEPRIBADIAN TERHADAP KINERJA DOSEN FAKULTAS TEKNIK UNNES - Abdullah, Haris (Food Science and Culinary Education Journal, 2013)
Professional lecturer must have a good performance, including lecturer Tech Faculty Unnes. lecturer performance among those influence by teaching competency and personality competency. Research objectives were to determine 1) how the level of teaching competency, personality competency, and lecturer performance, 2) the effect of teaching competency on lecturer performance, 3) the effect of personality competency on lecturer performance, 4) the effect of teaching competency and personality competency on lecturer performance, 5) relative contributions, 6) effective contributions. The sampling technique used purposive sampling with a sample population of 41 lecturers of 164 lecturers. The independent variable (teaching competency and personality competency), the dependent variable (lecturer performance). Collecting data using a structured questionnaire.  Data analysis using descriptive percentage, partial regression and multiple regression. Observational result; 1) teaching competency, personality competency, and lecturer performance is high with average point 3,76, 3,74 and 3,84; 2) have effect of teaching competency on the lecturer performances, p 0,00;  3) have effect of personality competency on the lecturer performances, p 0,00; 4) have effect of teaching competency and personality competency on the lecturer performances, p 0,00; 5) relative contributions teaching competency 56%, personality competency 44%; 6) effective contributions teaching competency 53,03%, personality competency 41,67%. Suggestion; 1) lecturer FT always upgrade performance’s; 2) Lecturer better engage students in research activitiesProfessional lecturer must have a good performance, including lecturer Tech Faculty Unnes. lecturer performance among those influence by teaching competency and personality competency. Research objectives were to determine 1) how the level of teaching competency, personality competency, and lecturer performance, 2) the effect of teaching competency on lecturer performance, 3) the effect of personality competency on lecturer performance, 4) the effect of teaching competency and personality competency on lecturer performance, 5) relative contributions, 6) effective contributions. The sampling technique used purposive sampling with a sample population of 41 lecturers of 164 lecturers. The independent variable (teaching competency and personality competency), the dependent variable (lecturer performance). Collecting data using a structured questionnaire.  Data analysis using descriptive percentage, partial regression and multiple regression. Observational result; 1) teaching competency, personality competency, and lecturer performance is high with average point 3,76, 3,74 and 3,84; 2) have effect of teaching competency on the lecturer performances, p 0,00;  3) have effect of personality competency on the lecturer performances, p 0,00; 4) have effect of teaching competency and personality competency on the lecturer performances, p 0,00; 5) relative contributions teaching competency 56%, personality competency 44%; 6) effective contributions teaching competency 53,03%, personality competency 41,67%. Suggestion; 1) lecturer FT always upgrade performance’s; 2) Lecturer better engage students in research activities